Depiction of a Shaiva image - Temples of India Project Team (Jio Institute, 2024)
This enigmatic deity, seemingly Shaiva, is depicted with six heads and twelve hands. Although all hands are broken, one appears to hold an attribute in the form of a trident. The waist portion is buried in the earth. The headgear includes a jatamukuta on the four side heads typically associated with Shiva, and a kirita-mukuta on the front and back heads, typically associated with Vishnu. While five faces exhibit a fierce form, one appears benevolent. The depiction resembles the Sadashiva form of Shiva, which includes five faces representing Ishan, Tatpurusha, Aghora, Vamadeva and Sadyojata, portrayed through fierce and benevolent expressions. However, labelling this image as a clear syncretic mixture of Sadashiva and Vishnu is difficult due to the placement of the kirita-mukuta above the fierce face types as well. This enigmatic image likely has Tantric associations, as evidenced by other images at the hill bearing Tantric connotations.